Microstructural evolution and bonding mechanisms of the brazed Ti/ZrO2 joint using an Ag68.8Cu26.7Ti4.5 interlayer at 900 °C. Issue 5 (28th February 2014) - Wei, Shen-Hung; Lin, Chien-Cheng
Abstract: Abstract : In this study, 3 mol% Y2 O3 -stabilized zirconia (3Y–ZrO2 ) and commercially pure titanium (cp-Ti) joints were fabricated with an Ag68.8 Cu26.7 Ti4.5 interlayer (Ticusil) at 900 °C for various brazing periods. After brazing at 900 °C/0.1 h, Ti2 Cu, TiCu, Ti3 Cu4, and TiCu4 layers were present at the Ti/Ticusil interface, while TiCu and TiO layers were observed at the Ticusil/3Y–ZrO2 interface. In the residual interlayer, clumpy TiCu4 was formed along with the Ag solid phase. After brazing at 900 °C/1 h, Ti3 Cu3 O and Ti2 O layers were formed at the interlayer/ZrO2 interface, while Cu2 O was precipitated in the residual interlayer with [ 111 ]_Cu_2 O //[ 111 ]_Ag and ( 202 )_Cu_2 O //( 202 )_Ag . After brazing at 900 °C/6 h, a two-phase (α-Ti + Ti2 Cu) region was observed on the Ti side with [ 2110 ]_α - Ti //[ 100 ]_Ti_2 Cu and ( 0002 )_α - Ti //( 013 )_Ti_2 Cu, while the TiCu layer grew at the expense of Ti3 Cu4 and TiCu4 . The bonding mechanisms and diffusion paths were explored with the aid of Ag–Cu–Ti and Ti–Cu–O ternary phase diagrams.